STUDI PERBANDINGAN GELOMBANG DI PPI DONGGALA DENGAN MENGGUNAKAN METODE GUMBEL DAN METODE WEIBULL - Setiyawan; Nurkhalisah (Jurusan Teknik Sipil, Fakultas Teknik, Universitas Negeri Gorontalo, 2023)
The Donggala Fish Landing Port (PPI) in Central Sulawesi, located in Labuan Bajo Village, Banawa District, Donggala Regency, suffered damage from the 2018 earthquake and tsunami that affected Palu, Donggala, and surrounding areas, necessitating repairs. This study aims to determine wave heights at PPI Donggala and predict future wave occurrences using the Gumbel and Weibull methods. The analysis uses secondary data, specifically hourly wind data from PPI Donggala. The significant wave height (Hs) was 0.98 meters with a significant wave period (Ts) of 4.74 seconds in 2017, occurring in the north. For the Gumbel method, wave heights for return periods were: 0.802 meters for 2 years, 0.894 meters for 5 years, 0.954 meters for 10 years, 1.031 meters for 25 years, 1.088 meters for 50 years, and 1.145 meters for 100 years. Using the Weibull method, wave heights were 0.778 meters for 2 years, 0.872 meters for 5 years, 0.943 meters for 10 years, 1.037 meters for 25 years, 1.108 meters for 50 years, and 1.179 meters for 100 years. The comparison of the Root Mean Square Error (RMSE) values between the Gumbel and Weibull methods yielded an identical value of 1.110 meters, indicating that both methods are equally accurate for this analysis. This study provides essential data for planning and repairing the Donggala Fish Landing Port's dock facilities to withstand future wave conditions.